Effect of Dietary Supplementation of Soapnut (Sapindus mukorossi) on Nutrient Utilization and Body Weight of HF Crossbred Cattle - Rathod, Sunil V; Pandya, Paresh R; Mathukiya, Gaurang P; Sorathiya, Kalpesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was aimed to explore the effect of dietary supplementation of soapnut (Sapindus mukorossi) powder on nutrient utilization and body weight (BW) in cattle. Fifteen HF crossbred cattle of same age and sex were divided into three equal groups on the basis of BW and were offered three treatments for 70 days. The treatments were; T0: control TMR (roughage: concentrate ratio 65:35), T1: control TMR supplemented with 1% Soapnut powder, and T2: control TMR supplemented with 2% Soapnut powder. Among the treatments BW gain observed was higher with lower level of soapnut supplement compared to higher soapnut level and control diet. The study revealed no adverse effect of dietary supplementation of soapnut powder on dry matter and other nutrient intake. The digestibility of nutrients was also not affected, except fibre fractions. Digestibility of CF, NDF and hemicellulose was adversely affected by 2% followed by 1% soapnut powder supplementation in TMR over the control diet.